"I'm an ogre so I'm very hungry!" "I'm assistant ogre": The Social Function of Sibling Imitation in Early Childhood. Issue 1 (16th June 2017) - Howe, Nina; Rosciszewska, Joanna; Persram, Ryan J.
Abstract : Siblings' imitative behaviors were investigated in 39 middle‐class dyads during six 90‐min home sessions at both Time 1 ( M age: older sibling = 4.4 years; younger sibling = 2.4 years) and Time 2 (2 years later). Although younger siblings imitated most often at T1 and T2, older siblings' imitation increased proportionally over time in comparison to younger siblings. Findings highlight the affiliative nature of imitation that occurred during reciprocal play interactions, via positive responses, and the content of the imitation. Finally, age was controlled by comparing first‐born siblings aged 4 at T1 to second‐born siblings aged 4 at T2. Findings demonstrated that sibling imitation had distinct characteristics despite the age match and partner effects. Sibling imitation is a dynamic, interactive social behavior and may be a powerful source of learning for young children. Highlights: The role of sibling imitation in ongoing play in early childhood is highlighted. Sibling imitation is a dynamic and affiliative behavior that promotes interaction during play. Naturalistic observations of sibling imitation document that it is a powerful source of learning for young children.